Deception Cove [large type] - Castle, Jayne (Castle, Jayne. Rainshadow novel., 2014)
As a light-talent, Alice North has the rare ability to make things disappear, including herself -- a gift that comes in handy during her magic act with her dust bunny Houdini. Business mogul Drake Sebastian is day-blind, since his sight was nearly destroyed in a lab accident. But he's the one man who can see Alice when she disappears -- and he needs her. On Rainshadow Island, two dangerous Old World crystals are missing, igniting a paranormal storm. Drake thinks Alice is the key to finding them, and proposes they head there, but only after a Marriage of Convenience. Alice's honeymoon on Rainshadow is guaranteed to be memorable, as the island -- and the passion between her and Drake -- is about to explode.